Gambaran Kadar Glukosa pada Penderita Obesitas - Rina Setyawati (Syntax Corporation Indonesia, 2021)
Obesity or excess body weight is a predisposing factor for various diseases, one of which is because the accumulation of fatty tissue causes insulin resistance and causes an increase in sugar levels. This study aims to determine the description of glucose levels in obese patients. This research method is carried out through literature review that comes from various related studies, the stages starting from data collection, deepening the problem to be studied, then processing and analyzing the data obtained. From the literature results obtained several descriptions of glucose levels with various criteria for different respondents. Based on the description of various research results, it is found that there are differences in the value of blood sugar levels in obese and non-obese people and there is no relationship between physical activity and fasting blood glucose levels in DM patients